Onde está o teu Deus? um estudo exegético dos Salmos 42 43 - Suave, Tonyglei (2012)
The objective of this dissertation is to present an exegetic study of a biblical poem: Psalm 42 43. This undertaking is justified in the measure that the search for the original meaning of a text which is inspired by God and is the bearer of a universal message of salvation can favor reflection on one of the problems that most disturbs the human conscience: human suffering and faith in a God who is omnipotent and filled with benevolence. Due to the particular position of this poem [at the start of the section of the Psalter which proportionally speaks most of human suffering] and certain stylistic traces [the striking comparison at the beginning of the poem; the name of God mentioned 22 times; the tetragram in the middle of it to call attention to a particular attitude of the person praying] this research has as a hypothesis that these Psalms throw some light on the subject of God s presence in the lives of people who suffer. In the style of commentary, the research continues following the steps of synchronic analysis with some reference to diachronic analysis when necessary. It analyzing the literary beauty and certain cultural, historical and theological aspects of one of the sacred texts which was chosen as a model of prayer for Israel because it deals with one of the vital problems of the human being in a realistic and beautiful manner. As a result of this work five essential elements were discovered which appear to contribute towards reflection on the presence of God next to the suffering human person: 1) the importance of trust in God; 2) how the presence of God appears to be experienced as absence; 3) worship as a privileged manner of communication and communion with God; 4) the misunderstanding of God as one of the causes of the difficulty to deal with suffering; 5) confining the presence of God to only the Temple in Jerusalem as a theological limitation of this poem